2012
DOI: 10.1007/s10546-012-9728-3
|View full text |Cite
|
Sign up to set email alerts
|

A Double-Canyon Radiation Scheme for Multi-Layer Urban Canopy Models

Abstract: We develop a double-canyon radiation scheme (DCEP) for urban canopy models embedded in mesoscale numerical models based on the Building Effect Parametrization (BEP). The new scheme calculates the incoming and outgoing longwave and shortwave radiation for roof, wall and ground surfaces for an urban street canyon characterized by its street and building width, canyon length, and the building height distribution. The scheme introduces the radiative interaction of two neighbouring urban canyons allowing the full i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
73
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 65 publications
(74 citation statements)
references
References 27 publications
1
73
0
Order By: Relevance
“…This effort helped to identify the dominant physical processes, the level of complexity needed in an application specific context, and parameter requirements. Other ULSM evaluations in online mode (coupled to an atmospheric/climate model) include: a single‐ and a multi‐layer urban parametrization within the Coupled Ocean–Atmosphere Mesoscale Prediction System for the New York City metropolitan area (Holt and Pullen, 2007); various urban canopy schemes (slab, single‐layer and multi‐layer with and without a building energy model) in the Weather Research and Forecasting/Chemistry model to evaluate the regional climate and air quality of the Yangtze River Delta (China) (Liao et al , 2014), and high‐resolution regional climate simulations over Berlin (Germany) with the COSMO‐CLM regional climate model coupled to the Town Energy Budget (TEB) model (Trusilova et al , 2013, 2015), the Double Canyon Effect Parametrization (DCEP) scheme (Schubert and Grossman‐Clarke, 2012) and TERRA_URB (Wouters et al , 2015, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…This effort helped to identify the dominant physical processes, the level of complexity needed in an application specific context, and parameter requirements. Other ULSM evaluations in online mode (coupled to an atmospheric/climate model) include: a single‐ and a multi‐layer urban parametrization within the Coupled Ocean–Atmosphere Mesoscale Prediction System for the New York City metropolitan area (Holt and Pullen, 2007); various urban canopy schemes (slab, single‐layer and multi‐layer with and without a building energy model) in the Weather Research and Forecasting/Chemistry model to evaluate the regional climate and air quality of the Yangtze River Delta (China) (Liao et al , 2014), and high‐resolution regional climate simulations over Berlin (Germany) with the COSMO‐CLM regional climate model coupled to the Town Energy Budget (TEB) model (Trusilova et al , 2013, 2015), the Double Canyon Effect Parametrization (DCEP) scheme (Schubert and Grossman‐Clarke, 2012) and TERRA_URB (Wouters et al , 2015, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the investigation and evaluation of modelling the water balance for cities is limited as well (eg., Grimmond and Oke, 1991;Kanda et al, 2005;Nakayoshi et al, 2009;Demuzere et al, 2013). As a result, the representation of the urban water balance in existing urban land-surface parametrizations is very rudimentary: For instance, various urban models do not consider evaporation from the impervious surfaces as a first approximation to the reduction of ET in cities (Hénon et al, 2012;Martilli et al, 2002;Schubert et al, 2012). Up to now, the accuracy, validity and applicability of water-storage parametrizations employed in existing land-surface models (Masson, 2000;Kanda et al, 2005;Oleson et al, 2008;Demuzere et al, 2013Demuzere et al, , 2014a have not been investigated in detail.…”
Section: Introductionmentioning
confidence: 99%
“…To this end, we employ the non‐hydrostatic limited area model system COSMO (Consortium for Small‐scale Modelling) in Climate Mode (CCLM, Steppeler et al , ) coupled with a multilayer urban canopy model, the Double‐Canyon Effect parametrization scheme (DCEP, Schubert et al , ). Previous studies with CCLM and DCEP for Berlin (Germany) and Basel (Switzerland), showed that diurnal variation and magnitude of the UHI is represented well in the model during summer months (Schubert and Grossman‐Clarke, ; Schubert and Grossman‐Clarke, ; Trusilova et al , ).…”
Section: Introductionmentioning
confidence: 99%